2009
DOI: 10.1136/gut.2009.186817
|View full text |Cite
|
Sign up to set email alerts
|

The variable phenotype of the p.A16V mutation of cationic trypsinogen (PRSS1) in pancreatitis families

Abstract: Penetrance of p.A16V is highly variable and family dependent, suggesting it contributes to multigenic inheritance of a predisposition to pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Mutation A16V is associated with variable disease penetrance and was identified not only in hereditary pancreatitis families but also in sporadic cases with no family history, suggesting a weaker biochemical phenotype (27,28). The mutation is found in ϳ3% of PRSS1 mutation-positive pancreatitis cases, although a recent study from Denmark reported higher regional occurrence (29).…”
Section: Autoactivation Of Cationic Trypsinogen Mutants In Presence Omentioning
confidence: 86%
“…Mutation A16V is associated with variable disease penetrance and was identified not only in hereditary pancreatitis families but also in sporadic cases with no family history, suggesting a weaker biochemical phenotype (27,28). The mutation is found in ϳ3% of PRSS1 mutation-positive pancreatitis cases, although a recent study from Denmark reported higher regional occurrence (29).…”
Section: Autoactivation Of Cationic Trypsinogen Mutants In Presence Omentioning
confidence: 86%
“…The p. R122H mutation is the most common one, followed by the p.N29I mutation. The p.A16V (c.47C>T) mutation (Grocock et al 2010) is the third most common one, but has not been reported in Japanese subjects.…”
Section: Prss1 Mutationsmentioning
confidence: 99%
“…Much more is presently known about genetic risk factors. The most important ones are mutations in the cationic trypsinogen gene [2,13,14,15] which were the first identified cause of hereditary pancreatitis. In contrast to mutations in the cationic trypsin gene, a G191R mutation in the anionic trypsin gene (PRSS2) was shown to have a protective effect [16].…”
Section: Chronic Pancreatitismentioning
confidence: 99%